Handbook on modular coordination general principles, rules, applications. (Philippine Domestic Construction Board, 1992)
Offers a practical guide to modular coordination. The work provides basic information, modules and reference systems, design rules and conventions, sample plans and a list of reference materials. It is designed for reference by people with background in building design and construction.